Emil Hübner’s correspondence in the National Library of Spain - Moreno Benito, Arturo (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
Emil Hübner is an essential figure to understand the epigraphy and history of ancient Hispania to the point that his work has become a relevant known research topic in current scholarship. This paper presents and analyses Hübner’s manuscript epistolary production preserved in the Biblioteca Nacional de España. Its aim is to explore Hübner’s activity as an epigraphist, with special attention to his working methodology, personality and the relationships he built with his colleagues from the Iberian Peninsula that were vital to conclude the volume of the Corpus Inscriptionum Latinarum dedicated to Hispania.
Keywords: Emil Hübner; manuscripts; correspondence; latin epigraphy; Hispania